Flora of Nam Kading National Protected Area III: Begonia namkadingensis (Begoniaceae), a new species in limestone area - Yang, Chen-Jui; Tagane, Shuichiro; Souladeth, Phetlasy; Okabe, Norikazu; Hu, Jer-Ming; Yahara, Tetsukazu (Phytotaxa, 2018)
A new species of Begonia (Begoniaceae), B. namkadingensis, is described. This species was collected on moist mossy limestone rocks in the Nam Kading National Protected Area in central Laos during our field survey in 2017. The species resembles B. pteridiformis, which is endemic to Peninsular Thailand, but can be distinguished by its smaller habit, fewer and smaller leaves, less hairy stems and leaves, narrower inner dorsal tepal of pistillate flowers, fewer stamens, and smaller fruits.